El diseño multimedia como estrategia de posicionamiento en la industria gráfica publicitaria Latacungueña. - Mullo Chimbo, Nelson Gustavo (2023)
Most of the graphic industries in Latacunga city, according to the mapping done have a lack of audiovisual production in animation and Motion Graphics, by the ambiguity of these industries in offering the same (service for print media), found that they do not have a service based on multimedia, this for factors related to little knowledge and trained personnel, based on this context, was the perfect excuse to develop an audiovisual product based on multimedia, to offer a billboard of services based on digital advertising, to thereby create an alternative to local consumption invigorating that market. Therefore, the objective of this project was to analyze multimedia products as a new product portfolio based on digital advertising in Latacunga city. To meet the objective of the study, we worked under a qualitative, descriptive, non experimental approach, under a non-probabilistic sample by convenience, in addition to the mapping method, in which techniques and instruments were used in each of them for data collection. To support the resolution of this project it was necessary to implement a design methodology known as Design Thinking, which allowed the development of audiovisual products to go through its phases, and the prototyping process was developed in a linear sequence avoiding errors in the design process. In addition to speeding up the process of creation and elaboration of the final product. By means of the Motion Graphics resource, a product was obtained that combined with graphic elements such as kinetic typography, kinetic Motion Graphics, and the use of real images, in addition to the complements of the principles of animation, gave as a final result an innovative, audiovisual and visually striking campaign, created as a new alternative in digital advertising development capable of having an immediate visual and communicational impact as a digital product for social networks, which is currently used by many people.